2019
DOI: 10.1155/2019/7105084
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes among Kidney Transplant Recipients and after Graft Failure: A Single-Center Cohort Study in Brazil

Abstract: Background. The results of kidney transplantation are impacted by the categories of events responsible for patient death and graft failure. The objective of this study was to evaluate the causes of death and graft failure and outcomes after graft failure among kidney transplant recipients. Methodology. A retrospective cohort study was conducted with 944 patients who underwent kidney transplantation. Outcomes were categorized in a managed and hierarchical manner. Results. The crude mortality rate was 10.8% (n=1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 39 publications
1
20
0
2
Order By: Relevance
“…The overall rate of acute rejection episodes (ARE) was 3.9% during the first year of renal transplant. Bicalho PR et al [18] in a recent study from Brazil reported ARE in 18.3% out of 944 patients with RT. Davidson et al [6] found that 29.7% of renal transplant patients developed ARE during the first year.…”
Section: Discussionmentioning
confidence: 92%
“…The overall rate of acute rejection episodes (ARE) was 3.9% during the first year of renal transplant. Bicalho PR et al [18] in a recent study from Brazil reported ARE in 18.3% out of 944 patients with RT. Davidson et al [6] found that 29.7% of renal transplant patients developed ARE during the first year.…”
Section: Discussionmentioning
confidence: 92%
“…In the second group, the clinical characteristics were collected over the time while the recipients had functioning grafts, such as: type of immunosuppression; delayed graft function (DGF) defined as dialysis requirement in the first week after transplantation; acute rejection (cellular or antibody-mediated) proved by biopsy or clinically defined; CMV infection and post-transplant diabetes; time for GL and its etiology categorized by chronic rejection, acute rejection, thrombosis, recurrence of underlying renal disease, and others. The type of GL was categorized as a failure (when the recipients had a functioning graft loss) or primary absence of graft function (in cases of thrombosis and primary nonfunction) according to previously published data [ 12 ]. Details about immunosuppression approach and prophylaxis are presented in S2 Appendix .…”
Section: Methodsmentioning
confidence: 99%
“…Despite this, long-term grafts and patient survival have not been followed in the same way, and GL due to chronic dysfunction and death with a functioning graft remain the main causes of long-term graft losses [9]. In emerging and developing countries, where transplantation has increased over the last few decades, death due to infections is the main cause of graft losses, while chronic dysfunction is the primary cause in countries with a high human development index [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…While dialysis techniques replace lost filtration capacities, which help remove toxins and regulate blood pressure and pH, transplantation is the ultimate solution to reinstate all innate kidney functions. Unfortunately, the severe global shortage of transplantable kidneys [6], as well as organ rejection [7] limit this ideal option and accentuate the demand for alternative solutions.…”
Section: Introductionmentioning
confidence: 99%